First Myotis lucifugus rabies virus variant detected in a human - Orciari, L.; Brown, C.; Lijewski, V.; Franka, R.; Jackson, F. R.; Niezgoda, M.; Track, D.; Yager, P. A.; Hightower, D.; Rupprecht, C. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
A 63 year old male from Barnstable County, MA was evaluated at Massachusetts tertiary care facility for possible stroke and encephalitis. Although the patient’s first symptoms were joint stiffness, within 2 days the patient was exhibiting signs of hydrophobia, and acute progressive encephalitis. Serum, CSF, nuchal (skin) biopsy, and saliva samples from the patient were sent to CDC for rabies diagnostic testing. No rabies virus IgG or IgM antibodies were detected in serum and CSF by the indirect fluorescent antibody (IFA) test, and no viral neutralizing antibodies were detected in the serum or CSF samples by the rapid fluorescent focus inhibition test (RFFIT). Rabies virus antigen was detected in nuchal biopsy samples using direct fluorescent antibody (DFA) test. Nested (and heminested) RT-PCR amplicons were produced from skin and saliva using multiple rabies virus nucleoprotein gene primers sets. Sequence analysis of the entire nucleoprotein gene and comparisons with samples in the CDC database and Genbank indicated that the rabies virus variant was associated with Myotis sp bats. Further analysis of phylogenetic trees (1000) by Neighbor Joining, Maximum Parsimony and Maximum Likelihood indicated the variant was most parsimonious with the common “little brown bat” Myotis lucifugus. Postmortem brain tissues were positive for rabies virus antigen by the direct fluorescent antibody test. Antigenic typing with monoclonal antibodies to the rabies virus nucleoprotein was consistent with the previous results of a bat rabies variant, but lacked the resolution of genetic typing methods. Sequence analysis of the RT-PCR amplicons from the complete nucleoprotein gene were consistent with the previous findings of the variant seen in M. lucifugus. Although M. lucifugus is common in the US and frequently has had known encounters with humans and animals, this is the first documented case of this rabies virus variant in a human. In contrast to this unique finding, the rabies virus variant associated with a solitary bat with rare known human or animal encounters Lasionycteris noctivagans (silver-haired bat) has been responsible for most human rabies cases in the USA over the last 2 decades.